Formative E-Assessment in Plenary Lectures - Rune Johan Krumsvik; Kristine Ludvigsen (Universitetsforlaget, 2012)
Little is known about how subjective and objective learning outcomes in plenary lectures are related in the Quality Framework of Higher Education and how they are influenced by formative e-assessment. Given the increasing focus on digitalisation and formative assessment in higher education and the increasing diversity among university students, questions relating to these topics should also be explored within plenary lectures. These lectures constitute the most formal, defined and "bounded" educational practice at universities and it is important to study the question of whether the relationship between student diversity, pedagogy and technology can re-define some of the pedagogical underpinnings that are historically associated with lecturer-centred pedagogy. This paper aims to identify: (1) factors that influence the relationship between intended and subjective learning outcomes in plenary lectures; and (2) how formative e-assessment may improve moments of contingency by increasing the consistency between intended and subjective learning outcomes. The results of this study show that audience response systems (ARS) can enhance formative e-assessment in plenary lectures and reduce the discrepancy between the intended learning outcome and the subjective learning outcome in such lectures with several hundred students. The implications of the current paper are twofold: first, a better understanding of similarities and dissimilarities in students' learning processes in plenary lectures and how these processes may be affected by formative e-assessment has implications for the planning and implementation of teaching and learning in higher education. Second, this has implications for how we can reduce the discrepancy between the intended, subjective and objective learning outcomes in plenary lectures.